A facile turn-on luminescence technique to trap hydrazine and its application in button mushroom (Agaricus bisporus). (21st March 2023) - Ghosh, Priyotosh; Dey, Koushik Kumar; Chattopadhyay, Ansuman; Sahoo, Prithidipa
Abstract : A novel carbazole–coumarin framework (CCF) chemodosimeter was designed for the selective detection of hydrazine in edible button mushrooms. Abstract : A novel carbazole–coumarin framework (CCF) has been designed for the detection of the environmental toxicant hydrazine. CCF exhibits excellent sensing behavior towards hydrazine in the presence of various nucleophilic and other relevant ions, having a detection limit in the nanomolar range. It interacts with hydrazine in a unique pathway where two hydrazine molecules simultaneously interact with it in two different sites through a chemodosimetric mechanism. The interaction yielded a vibrant turn-on blue fluorescence that was confirmed by both experimental studies and theoretical calculations. CCF has successfully been used to estimate the concentration of accumulated hydrazine in the gills of button mushrooms. The simple paper strips could be of practical use for the detection of hydrazine in both liquid and gas phases.